Stereological analysis of the cochlear nuclei of monkey (Macaca fascicularis) after deafferentation - Insausti, Ana M (Image analysis and stereology, 2000)
The cochlear nuclei (CN) in the brainstem receive the input signals from the inner ear through the cochlear nerve, and transmit these signals to higher auditory centres. A variety of lesions of the cochlear nerve cause deafness. As reported in the literature, artificial removal of auditive input, or 'deafferentation', induces structural alterations in the CN. The purpose of this study was to estimate a number of relevant stereological parameters of the CN in control and deafferented Macaca fascicularis monkeys.
Keywords: Cochlear nucleus; hearing; sluh; slušni aparat; Anatomy and histology; Drug effects; slušni živec; stereologija; Haplorhini; Cochlear nerve; analiza slik; opice; Pathology; Macaca fascicularis; Deafness; Neuroglia; Neurons; Histological techniques